Results of 1001 liver transplantations in 23 years: Ege University experience - Zeytunlu, Murat; Uğuz, Alper; Ünalp, Ömer; Ergün, Orkan; Karasu, Zeki; Günşar, Fulya; Akarca, Ulus; Yılmaz, Funda; Turan, İlker; Nart, Deniz; Tekin, Fatih; Özütemiz, Ömer; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Liver transplantation (LT) is now the standard of care for most end-stage liver diseases. Over the next 30 years, advances in medicine and technology will greatly improve the survival rates of patients after this procedure. The aim of the present study was to analyze retrospectively the results of 1001 patients withLT. Materials and Methods: Medical reports of 989 patients were analyzed retrospectively. Data were obtained from the patient’s data chart. Descriptive statistics were used to describe continuous variables (mean, median, and standard deviation). Results: A total of 1001 LTs for 989 recipients were performed at Ege University Organ Transplantation and Research Center between 1994 and 2017. Therewere 639 male and 350 female recipients. Among 1001 LTs, there were 438 deceased donors and 563 living donors. The age interval of the patients was 4 months to 71 years old. The median Model for End-Stage Liver Disease score was 20. There were 12 deceased liver donors using the split method. There were 12 cases subject to retransplantation. In living donor LT grafts, 423 right lobes, 46 left lobes, and 94 left lateral sectors were used. In the first monitoring,the total annual mortality rate was 130 cases (13%). The mortality rate in retransplantation was found to be 66%. A 1-year survival rate of 87% was generally established. Conclusion: LThas been improving consistently over the last two decades. Ege University is one of the biggest liver transplant centers in Turkey for both technical and educational perspective. Cite this article as: Zeytunlu M, Uğuz A, Ünalp Ö, et al. Results of 1001 liver transplantations in 23 years: Ege University experience. Turk J Gastroenterol 2018; 29: 664-8.